Structural behavior of supported tubular bus structure in substations under seismic loading. (1st November 2018) - Sun, Qilin; Yuan, Guanglin; Huang, Yuner; Shu, Qianjin; Li, Qingtao
Highlights: Quasi-static tests of temperature members under cyclic loading were conducted. Ground motion simulation experiments of substation system were conducted. Numerical analysis on supported bus structure under earthquakes were performed. Design recommendations for supported tubular bus structure were proposed. Abstract: This paper presents an experimental investigation on structural behavior of a temperature member used to interconnect the supported tubular bus structure of 220 kV substation, and the dynamic interaction between the components of a bus insulator substructure under seismic loading. Finite element (FE) analysis was performed to analyze the seismic stress of the supported tubular bus structure. The results of quasi-static experiments showed an elastic deformation characteristic, while the temperature member exhibited a damping ratio of 4–7%, and elastic stiffness of 13.4 N/mm. Compared with the stand-alone configuration, the peak accelerations of insulators connected to the tubular bus through the temperature member were reduced by 10–30%, while the maximum displacements were reduced by 30%. The maximum displacement responses of insulators connected to the tubular bus through clips were roughly the same as those under the stand-alone configuration, while the peak accelerations were reduced by 30–50%. When the ground acceleration reached the value of 6.2 m/s 2, the root stress exceeded the yield strength of the material. Under this condition the insulators may experience fracture or collapse.